2011
DOI: 10.1111/j.1365-2966.2011.18882.x
|View full text |Cite
|
Sign up to set email alerts
|

Non-Gaussianity and direction-dependent systematics in HST Key Project data

Abstract: Two new statistics, namely Δ and Δχ, based on the extreme value theory, were derived by Gupta et al. We use these statistics to study the direction dependence in the HST Key Project data, which provides one of the most precise measurements of the Hubble constant. We also study the non‐Gaussianity in this data set using these statistics. Our results for Δ show that the significance of direction‐dependent systematics is restricted to well below the 1σ confidence limit; however, the presence of non‐Gaussian featu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…• Using HST key project data McClure & Dyer (2007) showed that a statistically significant variation of at least 9 km/s/Mpc exists in the observed value of H0 with a directional uncertainty of about 10-20%. Gupta, Saini (2011) also found directional dependence in the HST key project data.…”
Section: Introductionmentioning
confidence: 73%
“…• Using HST key project data McClure & Dyer (2007) showed that a statistically significant variation of at least 9 km/s/Mpc exists in the observed value of H0 with a directional uncertainty of about 10-20%. Gupta, Saini (2011) also found directional dependence in the HST key project data.…”
Section: Introductionmentioning
confidence: 73%
“…The variation does not appear to be an artifact of the Galactic dust; and the overall structure in the map is not consistent with the distribution of dust in the Cosmic Background Explorer (COBE) map [4]. Using techniques based on extreme value theory [5], [6] have reported that the errors in HST key project data are non-Gaussian.…”
Section: Introductionmentioning
confidence: 90%